1998
DOI: 10.1021/bi981412b
|View full text |Cite
|
Sign up to set email alerts
|

Use of Site-Directed Mutagenesis To Identify Residues Specific for Each Reaction Catalyzed by Chorismate Mutase−Prephenate Dehydrogenase from Escherichia coli

Abstract: Site-directed mutagenesis was performed on the bifunctional enzyme chorismate mutase-prephenate dehydrogenase in order to identify groups important for each of the two reactions. We selected two residues for mutagenesis, Lys37 and His131, identified previously by differential peptide mapping to be essential for activity [Christendat, D., and Turnbull, J. (1996) Biochemistry 35, 4468-4479]. Kinetic studies reveal that K37Q exhibits no mutase activity while retaining wild-type dehydrogenase activity, verifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
35
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 54 publications
(121 reference statements)
9
35
0
Order By: Relevance
“…Detailed kinetic and pH rate analysis for AroE shikimate dehydrogenase from the pea also displayed a similar pH rate profile (24). Active site lysine and histidine residues are known to titrate in this region (range pH 6.5 to 8.5); however, other active site groups, such as aspartate, can also titrate in this pH range depending on their environment (25). This observation is in agreement with the crystal structure of HI0607, which showed that Lys-67 and Asp-103 are located at the entrance of the substrate-binding pocket, the expected position for a catalytic group in this protein (Fig.…”
Section: Identification Of the Nucleotide And Substrate-binding Domains-mentioning
confidence: 80%
“…Detailed kinetic and pH rate analysis for AroE shikimate dehydrogenase from the pea also displayed a similar pH rate profile (24). Active site lysine and histidine residues are known to titrate in this region (range pH 6.5 to 8.5); however, other active site groups, such as aspartate, can also titrate in this pH range depending on their environment (25). This observation is in agreement with the crystal structure of HI0607, which showed that Lys-67 and Asp-103 are located at the entrance of the substrate-binding pocket, the expected position for a catalytic group in this protein (Fig.…”
Section: Identification Of the Nucleotide And Substrate-binding Domains-mentioning
confidence: 80%
“…An earlier report by Christendat et al [15] indicated that mutagenesis of several residues in the dehydrogenase portion of the T-protein significantly affected CM activity, either by reducing K cat (His189Asn) or elevating K m (His239Asn, His245Asn). The findings reported here suggest that additional amino acids in the PDH domain, extending beyond residue 336 effect mutase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies of the pH dependence of the kinetic parameters V and V/K indicate that a deprotonated group facilitates hydride transfer from prephenate to NAD ϩ by polarizing the 4-hydroxyl group of prephenate, whereas a protonated residue is required for binding prephenate to the enzyme⅐NAD ϩ complex (25). The conserved residues His-197 and Arg-294 have been identified through extensive mutagenesis studies to fulfill these two roles (26,27). Further analyses of the activities of wild-type protein and site-directed variants in the presence of a series of inhibitory substrate analogues support the idea that Arg-294 binds prephenate through the ring carboxylate (26).…”
mentioning
confidence: 99%